Extracellular matrix remodeling in patients with ischemic chronic heart failure with preserved ejection fraction - V. D. Syvolap; D. A. Lashkul (Zaporožskij Medicinskij Žurnal)
Aim. To identify features, relationships between parameters of the extracellular matrix and renal function in 110 patients with ischemic chronic heart failure the activity of collagen metabolism markers (MMP-9, TIMP-1, PICP), cystatin C, structural and functional parameters of the heart were studied using ELISA, echocardiography.